Mental health aspects of binge eating disorder: A cross-sectional mixed-methods study of binge eating disorder experts' perspectives - Bray, Brenna; Bray, Chris; Bradley, Ryan; Zwickey, Heather (Frontiers in Psychiatry, 2022)
Binge eating disorder has high comorbidity with a variety of mental health diagnoses and significantly impairs quality of life. This mixed-methods cross-sectional survey study aimed to collect information from experts in the field about mental health issues pertaining to adult binge eating disorder pathology. Fourteen expert binge eating disorder researchers and clinicians were identified based on history of NIH R01 funding, relevant PubMed-indexed publications, active practice in the field, leadership in related professional societies, and/or distinction in popular press. Semi-structured interviews were anonymously recorded and analyzed by ≥2 investigators using reflexive thematic analysis and quantification. The domains of depression, anxiety, attention deficit disorder (ADD)/attention deficit hyperactive disorder (ADHD), substance-related and addictive disorders (SRADs), obsessive-compulsive disorder (OCD), and post-traumatic stress disorder (PTSD) were addressed in relation to binge eating disorder pathology by 100%, 100%, 93%, 79%, 71%, and 64% of participants respectively. Depression and anxiety seem to be the most commonly recognized mental health comorbidities among experts participating in this study. These expert perceptions generally align with the most comprehensive and up-to-date information available on mental health comorbidity prevalence data in adult binge eating disorder, though updated surveys are warranted. The findings from this study highlight the importance of screening for eating disorders among individuals with Axis-I mental health diagnoses (e.g., depression and other mood disorders, anxiety disorders, ADD/ADHD, and SRADs). Research on underlying mechanisms that link various Axis-I disorders to binge eating disorder is also warranted and recommended by the experts.